Microsurgery: A 10-Year Experience with Loupe Magnification - Nangole, Ferdinand Wanjala; Khainga, Stanley Ominde (Journal of Reconstructive Microsurgery Open, 2020)
Background Microsurgical procedures are still rare in many countries especially in resource-constrained countries. Among reasons for this is the unavailability of operating microscopes that are costly. Operating loupes are considered inferior to the microscope and are most discouraged for many microsurgical procedures. We audit patients operated under loupes for the past 10 years and present our findings.Patients and Methods This was a prospective audit of patients who underwent microsurgical reconstructive procedures in the plastic surgery unit at Kenyatta National Hospital between January 2009 and December 2019.Results A total of 352 patients with 360 procedures were done over a 10-year period. The age range for the patients was 5 to 90 years. Free flaps accounted for 78% of the surgical procedures (n = 298) followed by nerve repairs 8.8% (n = 32) and reimplantation surgeries 8.5% (n = 30). The overall success rate for free flaps was 93.3% with reimplantations of 77%.Conclusion Microsurgical reconstructive procedures as demonstrated in this study can safely be done with loupes. Loupes provide an alternative means of magnification that is cost effective and cheaper. In good hands, good surgical outcomes can be achieved that are comparable to the operating microscopes.
Keywords: microsurgery; free flaps; reimplantation; loupes